Benign cystic peritoneal mesothelioma - Shetty, Santhosh; H, Nagaraj; Prabhakar, Sneha Priya; Rajput, Akarsh (International Journal of Research in Medical Sciences, 2017)
A well-defined but rare entity of Benign Cystic Peritoneal Mesothelioma (BCPM) is reported. The aetiology of this neoplasm remains obscure. The presenting features make a precise preoperative diagnosis difficult but information provided by computed tomography and cytology may help. A firm diagnosis can only come from an electronic microscopy or immunohistological examination of the tumour. Diagnostic accuracy and diligent follow up are essential because, although the tumour is considered benign, it does tend towards local recurrence.